Analysis Of The Causes Of High Inpatient Claim Ratio At Intra Asia Insurance In 2024 - Fresitinawati, Senintyas; Nurrahim, Eka Julianti; Setiawan, Muhammad Raja Nararya; Rakhman, Sitti (Jurnal Multidisiplin Sahombu, 2025)
PT. Intra Asia, located in South Jakarta, offers health insurance products such as outpatient, inpatient, dental care, glasses, and maternity coverage. Since its launch in 2017, the company has served 17 clients, including new and renewal accounts. Its market focuses on companies providing additional health protection for employees. In 2022, five client companies reported a claim ratio exceeding 120%, with inpatient claims averaging over 90% and surpassing outpatient claims in 2023. Data for December 2023 shows 5,234 outpatient claims and 2,503 inpatient claims. In 2024, 142 inpatient claims were reported, with 97 cases (5%) experiencing lost monitoring, contributing to extended hospital stays and higher costs. The issue stems from insufficient monitoring due to reliance on third-party administrators (TPAs). While the company adheres to its SOPs, including regular claim ratio reviews (every 3–6 months), gaps in monitoring at hospitals have led to inflated inpatient costs, emphasizing the need for stricter follow-ups.